High-rate nickel-based positive electrode material, preparation method and application thereof
Patent Information
- Application Number
- CN202211285752.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-20
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2042-10-20
AI Technical Summary
The poor rate performance of existing nickel-based ternary materials affects the charge and discharge rates of lithium-ion batteries, limiting their application in high-end equipment.
Using the chemical composition of LiaNixCoyMzTpO2, group IIIB and group VA elements are doped into the lattice of nickel-based cathode materials. Nickel-based cathode materials are prepared through co-precipitation reaction and calcination to improve the lithium-ion and electron migration rates.
It improves the rate performance of nickel-based cathode materials, enabling them to achieve 95.2% of the discharge capacity at 0.1C rate at 1C rate, making them suitable for high-rate lithium-ion batteries.
Smart Images

Figure CN117954619B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion batteries, specifically to a high-rate nickel-based cathode material, its preparation method, and its application. Background Technology
[0002] Among numerous chemical power sources, lithium-ion batteries have garnered widespread attention due to their advantages such as high energy density, long lifespan, low self-discharge, absence of memory effect, and environmental friendliness. Since Sony first successfully commercialized lithium-ion battery technology in 1991, lithium-ion batteries have been widely used in consumer electronic devices such as mobile phones, laptops, and cameras. In recent years, the vigorous promotion of electric vehicles has driven explosive growth in the power battery market.
[0003] Lithium-ion batteries suffer from long charging times and slow charge / discharge rates, significantly impacting the user experience of mobile phones, electric vehicles, and other applications. Power batteries primarily consist of a positive electrode, negative electrode, separator, and electrolyte. The positive electrode material is the key component determining the charge / discharge rate of the power battery. Among the most commonly used positive electrode materials in commercially available lithium-ion batteries, such as LiCoO2, LiFePO4, and ternary materials, nickel-based ternary materials offer the advantage of high energy density, meeting the requirements of high-end lithium-ion batteries. However, their rate performance needs further improvement. Therefore, the development of high-rate nickel-based positive electrode materials is of great significance for further enhancing the user experience of lithium-ion batteries. Summary of the Invention
[0004] The purpose of this invention is to overcome the problem of poor rate performance of nickel-based ternary materials in the prior art, and to provide a high-rate nickel-based cathode material, its preparation method and application. This nickel-based cathode material has good electrochemical performance when applied in lithium-ion batteries, specifically in that its rate discharge performance is improved.
[0005] To achieve the above objectives, a first aspect of the present invention provides a nickel-based cathode material, wherein the chemical composition of the nickel-based cathode material is Li. a Ni x Co y M z T p O2; wherein, 0.9≤a≤1.3, 0<x≤1, 0≤y<1, 0≤z<1, 0<p≤0.1, and x+y+z=1; M is selected from at least one of group VIIB and group IIIA elements, T is selected from at least one of group IIIB and group VA elements, and T is doped in the lattice of the nickel-based cathode material.
[0006] A second aspect of the present invention provides a method for preparing a nickel-based cathode material, the method comprising the following steps:
[0007] (1) A precursor is obtained by co-precipitating a metal salt solution, a precipitant solution and a complexing agent solution;
[0008] (2) The precursor, the T-containing compound, the lithium source and the solvent are mixed, dried and calcined to obtain the nickel-based cathode material;
[0009] The metal salt solution contains at least one of Ni, Co, and M, where M is selected from at least one of Group VIIB and Group IIIA elements; and T is selected from at least one of Group IIIB and Group VA elements.
[0010] The third aspect of this invention provides the application of the nickel-based cathode material described in the first aspect or the nickel-based cathode material prepared by the method described in the second aspect in lithium-ion batteries.
[0011] Through the above technical solution, the present invention can achieve the following beneficial effects:
[0012] The nickel-based cathode material provided by this invention differs from existing cathode materials in that it has a novel composition and structure. It contains at least one element from Group IIIB and Group VA, which is doped into the nickel-based cathode material lattice, resulting in a lower lithium-nickel mixing degree and higher (110) crystal plane exposure. When applied to lithium-ion batteries, it can improve the migration rate of lithium ions and electrons in the cathode material, thereby enhancing the electrochemical performance of the lithium-ion battery. Furthermore, the preparation method of the nickel-based cathode material provided by this invention is simple and easy to operate.
[0013] The nickel-based cathode material provided by this invention exhibits excellent electrochemical performance, particularly high rate capability. Its discharge capacity at 1C rate reaches 95.2% of the discharge capacity at 0.1C rate. This novel nickel-based cathode material can be used in high-rate lithium-ion batteries. Attached Figure Description
[0014] Figure 1 This is a SEM image of the nickel-based cathode material prepared in Example 1 of this invention;
[0015] Figure 2 This is the XRD pattern of the nickel-based cathode material prepared in Example 1 of the present invention;
[0016] Figure 3 This is a SEM image of the nickel-based cathode material prepared in Example 2 of this invention;
[0017] Figure 4 This is the XRD pattern of the nickel-based cathode material prepared in Example 2 of the present invention;
[0018] Figure 5 This is a graph showing the change in the concentration of the complexing agent in the coprecipitation reaction system of Example 1 of the present invention over the reaction time. Detailed Implementation
[0019] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0020] The first aspect of this invention provides a nickel-based cathode material, wherein the chemical composition of the nickel-based cathode material is Li. a Ni x Co y M z T p O2; wherein, 0.9≤a≤1.3, 0<x≤1, 0≤y<1, 0≤z<1, 0<p≤0.1, and x+y+z=1; M is selected from at least one of group VIIB and group IIIA elements, T is selected from at least one of group IIIB and group VA elements, and T is doped in the lattice of the nickel-based cathode material.
[0021] In this invention, the T doping in the nickel-based cathode material lattice refers to the presence of the T element in the crystal structure of the cathode material, which can be determined by XRD characterization. The XRD pattern shows that there are no impurity peaks in the nickel-based cathode material, indicating that the added T component has completely entered the material's crystal lattice.
[0022] In a preferred embodiment of the present invention, the chemical composition is Li. a Ni x Co y M z T p The nickel-based cathode material of O2 has the following properties: 0.9 ≤ a ≤ 1.3, 0.5 ≤ x ≤ 0.95, 0 ≤ y ≤ 0.5, 0 ≤ z ≤ 0.5, 0 < p ≤ 0.05, and x + y + z = 1. The values of a, x, y, z, and q satisfy the principle of electroneutrality. In this invention, a can be 0.9, 1, 1.1, 1.2, 1.3, or any value between any two. x can be 0.5, 0.6, 0.7, 0.8, 0.9, 0.95, or any value between any two. y can be 0, 0.1, 0.2, 0.3, 0.4, 0.5, or any value between any two. z can be 0, 0.1, 0.2, 0.3, 0.4, 0.5, or any value between any two. p can be 0.01, 0.02, 0.03, 0.04, 0.05, or any value between any two of them.
[0023] The present invention selects a wide range of types of T. In a preferred embodiment of the present invention, T is selected from at least one of Bi, Sc, and Y. Using at least one of Bi, Sc, and Y is more beneficial to improving the rate performance of the cathode material.
[0024] In a preferred embodiment of the present invention, M is selected from Mn and / or Al. That is, the chemical composition is Li. a Ni x Co y M z T p The preferred nickel-based cathode material for O2 is Li. a Ni x Co y Mn z T p O2 and / or Li a Ni x Co y Al z T p O2.
[0025] In a preferred embodiment of the present invention, in the X-ray diffraction (XRD) pattern of the nickel-based cathode material, the ratio of the intensities of the (003) and (104) crystal plane diffraction peaks, measured by peak height, is not less than 1.5, preferably not less than 1.7, and more preferably not less than 1.75.
[0026] In a preferred embodiment of the present invention, in the XRD pattern of the nickel-based cathode material, the ratio of the intensity of the (110) and (108) crystal plane diffraction peaks, measured by peak height, is not less than 1, preferably not less than 1.05, and more preferably not less than 1.1.
[0027] The nickel-based cathode material with the above-mentioned preferred ratio of diffraction peak indices has a more perfect crystal structure and better rate performance. The materials provided in the prior art cannot guarantee that the ratio of the indices of the (003) and (104) diffraction peaks and the ratio of the indices of the (110) and (108) diffraction peaks will both remain at a high level.
[0028] In this invention, the XRD pattern of the nickel-based cathode material was obtained using a Bruker D8Advance SS X-ray diffractometer. The ratio of the intensities of the diffraction peaks on each crystal plane refers to the ratio of the peak heights of the diffraction peaks on each crystal plane.
[0029] In a preferred embodiment, the XRD diffraction pattern of the nickel-based cathode material is as follows: Figure 2As shown in the figure, the main diffraction peaks of the nickel-based cathode material are consistent with those of the hexagonal α-NaFeO2 structure, indicating the formation of a good layered crystal structure. The intensity ratio of the (003) diffraction peak in the 2θ range of 18°-20° to the (104) diffraction peak in the 43.5°-45° range is 1.99, indicating a very low lithium-nickel mixing ratio in the nickel-based cathode material. In the 2θ range of 63°-66°, the intensity ratio of the (110) diffraction peak in the (108) diffraction peak is 1.15, indicating that the (110) crystal plane is sufficiently exposed, which is beneficial for lithium ion migration in the nickel-based cathode material and can improve its rate performance.
[0030] In a preferred embodiment of the present invention, the nickel-based cathode material is a secondary microsphere formed by the agglomeration of primary particles, and the particle size of the secondary microsphere is 1-30 μm, preferably 1-20 μm.
[0031] In this invention, the size of the primary particles is not particularly limited; they can be nanoparticles, submicron-sized particles, or micron-sized particles. The arrangement of the primary particles is also not particularly limited; they can be irregularly arranged or arranged radially. Preferably, the size of the primary particles is 0.02-2 μm.
[0032] In this invention, the morphology of the nickel-based cathode material is characterized by scanning electron microscopy (SEM), using a ZEISS Merlin microscope (ZEISS GmbH, Germany). In a preferred embodiment, the SEM image of the nickel-based cathode material is shown below. Figure 1 As shown in the figure, the nickel-based cathode material provided by this invention consists of spherical particles, which are secondary microspheres formed by the aggregation of primary particles. The size of the primary particles is between 0.1 and 2 μm, and the size of the secondary microspheres is approximately 9.5 μm.
[0033] The inventors of this invention, through in-depth research on nickel-based cathode materials, discovered that when the chemical composition of the nickel-based cathode material is Li... a Ni x Co y M z T pO2, wherein M is selected from at least one element from Group VIIB and Group IIIA, T is selected from at least one element from Group IIIB and Group VA, and T is doped in the lattice of the nickel-based cathode material; and when the ratio of the intensities of the (003) and (104) diffraction peaks in the nickel-based cathode material is not less than 1.5, and the ratio of the intensities of the (110) and (108) diffraction peaks is not less than 1.0, the nickel-based cathode material has better rate performance and can be used in lithium-ion batteries with high rate discharge.
[0034] A second aspect of the present invention provides a method for preparing a nickel-based cathode material, the method comprising the following steps:
[0035] (1) A precursor is obtained by co-precipitating a metal salt solution, a precipitant solution and a complexing agent solution;
[0036] (2) The precursor, the T-containing compound, the lithium source and the solvent are mixed, dried and calcined to obtain the nickel-based cathode material;
[0037] The metal salt solution contains at least one of Ni, Co, and M, where M is selected from at least one of Group VIIB and Group IIIA elements; and T is selected from at least one of Group IIIB and Group VA elements.
[0038] The inventors of this invention discovered during the research on the preparation of nickel-based cathode materials that a cathode material precursor is first prepared through a co-precipitation reaction, and then the cathode material precursor is mixed with a T-containing compound, a lithium source, and a solvent, dried, and calcined to obtain a nickel-based cathode material with good rate performance.
[0039] In a preferred embodiment of the present invention, the coprecipitation reaction in step (1) includes: simultaneously adding a metal salt solution, a precipitant solution and a complexing agent solution to a reaction vessel under stirring to obtain a reaction product; then performing solid-liquid separation and drying on the reaction product to obtain a precursor.
[0040] In this invention, the metal salt solution contains at least one of Ni, Co, and M, wherein M is selected from at least one of Group VIIB and Group IIIA elements, preferably Mn and / or Al. The Ni, Co, and M elements exist in the form of nickel salt, cobalt salt, and M salt, respectively.
[0041] In this invention, there are no particular restrictions on the types of nickel salt, cobalt salt and M salt. Preferably, each of the nickel salt, cobalt salt and M salt is independently selected from at least one of their sulfate, nitrate, acetate, oxalate and hydrochloride salts. More preferably, the nickel salt, cobalt salt and M salt are selected from at least one of nickel sulfate, nickel nitrate, cobalt acetate, cobalt oxalate, manganese sulfate, manganese nitrate, aluminum nitrate, aluminum acetate and aluminum sulfate.
[0042] In a preferred embodiment of the present invention, the molar concentration of the metal salt solution, calculated based on metal elements, is 0.01-5 mol / L, preferably 0.01-4 mol / L, more preferably 0.5-4 mol / L, and for example, it can be 0.01 mol / L, 0.1 mol / L, 0.5 mol / L, 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L, and any value within the range formed by any two of these values.
[0043] In a preferred embodiment of the present invention, the molar ratio of Ni, Co and M in the metal salt solution is (0-1):(0-1):(0-1), preferably (0.5-0.95):(0-0.5):(0-0.5), wherein the molar amount of Ni is not 0.
[0044] In this invention, there are no particular limitations on the type of precipitant, as long as it can satisfy the precipitation reaction of the metal salt solution. Preferably, the precipitant is selected from at least one of alkali metal hydroxides, carbonates, and bicarbonates, and the alkali metal is preferably selected from at least one of Na, K, and Li; more preferably, the precipitant is selected from at least one of sodium hydroxide, sodium carbonate, sodium bicarbonate, potassium hydroxide, potassium carbonate, potassium bicarbonate, lithium hydroxide, lithium carbonate, and lithium bicarbonate. Sodium hydroxide is used as an example in this embodiment, but the invention is not limited thereto.
[0045] In this invention, there is no particular limitation on the concentration of the precipitant solution. Preferably, the concentration of the precipitant solution is 0.01-16 mol / L, for example, it can be 0.01 mol / L, 0.02 mol / L, 0.1 mol / L, 0.5 mol / L, 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L, 6 mol / L, 7 mol / L, 8 mol / L, 9 mol / L, 10 mol / L, 11 mol / L, 12 mol / L, 13 mol / L, 14 mol / L, 15 mol / L, 16 mol / L, and any value within any two of these values, preferably 2-12 mol / L.
[0046] In this invention, the type of complexing agent is not particularly limited and can be a compound that can form complexes with Ni, Co and M in aqueous solution; preferably, the complexing agent is selected from at least one of ammonium ion donors, alkanolamine complexing agents, aminocarboxylic acid complexing agents, hydroxyaminocarboxylic acid complexing agents, carboxylate complexing agents and thiocyanate complexing agents.
[0047] In a preferred embodiment of the present invention, the ammonium ion donor is selected from at least one of ammonia, ammonium oxalate, ammonium carbonate and ammonium hydroxide.
[0048] In a preferred embodiment of the present invention, the alkanolamine complexing agent is selected from at least one of ethanolamine, diethanolamine, 2-dibutylaminoethanol, 2-diethylaminoethanol and N,N-diethylethanolamine.
[0049] In a preferred embodiment of the present invention, the aminocarboxylic acid complexing agent is selected from at least one of sodium nitrilotriacetate (NTA), potassium nitrilotriacetate, ethylenediaminetetraacetic acid and its salts (EDTA), and diethylenetriaminepentaacetic acid (DTPA).
[0050] In a preferred embodiment of the present invention, the hydroxyaminocarboxylic acid complexing agent is selected from at least one of ethylenediaminetetraacetic acid (HEDTA) and its salts, ethylene glycol bis(β-diaminoethyl)ethyl ether-N,N,N'N'-tetraacetic acid (EGTA) and its salts, and dihydroxyglycine and its salts.
[0051] In a preferred embodiment of the present invention, the carboxylate complexing agent is selected from at least one of oxalic acid and its salts, tartaric acid and its salts, citric acid and its salts, gluconic acid and its salts, carboxymethyl hydroxymalonic acid (CMOM) and its salts, carboxymethyl hydroxysuccinic acid (CMOS) and its salts, and hydroxyethyl aminoacetic acid (DHEG) and its salts.
[0052] In a preferred embodiment of the present invention, the thiocyanate complexing agent is selected from at least one of sodium thiocyanate, potassium thiocyanate, ammonium thiocyanate, calcium thiocyanate, and zinc thiocyanate.
[0053] The present invention uses ammonia as a complexing agent as an example for illustrative purposes, but the present invention is not limited thereto.
[0054] In a preferred embodiment of the present invention, the concentration of the complexing agent solution is not particularly limited. Preferably, the concentration of the complexing agent solution is 0.01-16 mol / L, more preferably 2-15 mol / L. For example, it can be 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L, 6 mol / L, 7 mol / L, 8 mol / L, 9 mol / L, 10 mol / L, 11 mol / L, 12 mol / L, 13 mol / L, 14 mol / L, 15 mol / L, or any range between any two values.
[0055] In a preferred embodiment of the present invention, a base liquid is added to the reaction vessel before the metal salt solution, precipitant solution and complexing agent solution are added.
[0056] In a preferred embodiment of the present invention, the base liquid is an aqueous solution containing a complexing agent; the volume of the base liquid is 0-100% of the volume of the reaction vessel, preferably 0-80%, and more preferably 10-60%. The concentration of the complexing agent in the base liquid is 0-1.8 mol / L, preferably 0.05-1.5 mol / L, and more preferably 0.1-1 mol / L.
[0057] In a preferred embodiment of the present invention, the concentration of the complexing agent in the base solution is at least 0.05 mol / L lower than the concentration of the complexing agent at the end of the reaction, preferably at least 0.1 mol / L lower.
[0058] In a preferred embodiment of the present invention, the concentration of the complexing agent in the coprecipitation reaction system gradually increases, and the rate of change of the concentration of the complexing agent gradually decreases; the rate of change of the concentration of the complexing agent is below 1 mol / L·h, preferably 0.001-1 mol / L·h, and more preferably 0.001-0.5 mol / L·h.
[0059] In a preferred embodiment of the present invention, the total reaction time is denoted as R hours. In the first 1 / 8 of R hours after the start of the reaction, the concentration change rate of the complexing agent is not less than 0.021 mol / L·h, preferably 0.021-1 mol / L·h, more preferably 0.021-0.5 mol / L·h, for example 0.021 mol / L·h, 0.026 mol / L·h, 0.031 mol / L·h, 0.036 mol / L·h, 0.041 mol / L·h, 0.046 mol / L·h, 0.5 mol / L·h, and any value within the range formed by any two of these values.
[0060] In this invention, the "concentration change rate of the complexing agent" refers to the difference between the final concentration and the initial concentration of the complexing agent in the reaction system within any given time period, measured in hourly increments. The "gradually decreasing concentration change rate of the complexing agent in the coprecipitation reaction system" means that, from the moment the complexing agent is added to the end of the reaction, the concentration change rate of the complexing agent in the reaction system generally shows a gradually decreasing trend, but one or more local intervals are allowed; within these local intervals, the concentration change of the complexing agent in the reaction system exhibits different trends (e.g., remaining constant and / or gradually increasing and / or a disordered state). The premise is that the existence of such local intervals is unavoidable given the current level of technical development in this field, and the existence of these local intervals does not affect those skilled in the art from still determining that the concentration change rate of the complexing agent in the reaction system over the entire time period "(generally) shows a gradually decreasing trend." Furthermore, the existence of these local intervals does not affect the achievement of the intended purpose of this invention, is acceptable, and is also included within the scope of protection of this invention.
[0061] In a preferred embodiment of the present invention, the time from the addition of the complexing agent to reaching a concentration of not less than 80% of the complexing agent concentration at the end of the reaction in the precipitation reaction system does not exceed 1 / 4R hour.
[0062] In a preferred embodiment of the present invention, the concentration of the complexing agent at the end of the reaction is 0.05-2 mol / L, preferably 0.05-1.2 mol / L.
[0063] In this invention, to promote the full reaction of the metal salt solution, precipitant solution, and complexing agent solution, the conditions for the precipitation reaction include: a temperature of 20-70℃, preferably 45-60℃; a pH value of 8-14, preferably 10-12; a reaction time of not less than 10h, preferably 12-96h, more preferably 12-48h; and the precipitation reaction is carried out under stirring conditions at a stirring speed of 50-1200r / min, preferably 600-1200r / min.
[0064] It should be understood that pH control can be achieved by maintaining a constant pH during the reaction time, or by varying the pH of the reaction process according to product objectives. However, the pH variation range should be within the range of the reaction system described above. In a further preferred embodiment, the pH of the reaction system remains constant within the aforementioned range.
[0065] In a preferred embodiment of the present invention, the coprecipitation reaction time is denoted as R hours. During the first 1 / 8 of R hours of the reaction, the solid content of the precipitation reaction system is not higher than 7 wt%, preferably not higher than 5 wt%, for example, 0 wt%, 0.5 wt%, 1 wt%, 1.5 wt%, 2 wt%, 2.5 wt%, 3 wt%, 3.5 wt%, 4 wt%, 4.5 wt%, 5 wt%, and any value within the range formed by any two of these values.
[0066] In this invention, the solid content of the coprecipitation reaction system is related to the amount of metal salt solution, complexing agent solution and precipitant solution added, and the amount added is related to the flow rate and concentration of each material. Therefore, those skilled in the art can control the solid content of the coprecipitation reaction system by controlling the flow rate and concentration of the metal salt solution, complexing agent solution and precipitant solution.
[0067] This invention offers a wide range of options for the flow rates and concentrations of the metal salt solution, complexing agent solution, and precipitant solution, allowing those skilled in the art to control the flow rates and concentrations of each material as needed. In some preferred embodiments, given a fixed concentration of the metal salt solution, complexing agent solution, and precipitant solution, the initial volumetric flow rate ratio of the metal salt solution to the complexing agent solution is preferably set to 1-10, more preferably 2-6. Then, the flow rate of the metal salt solution is kept constant. By controlling the flow rate of the complexing agent, the concentration and rate of change of the complexing agent in the coprecipitation reaction system are kept within the aforementioned range. By controlling the flow rate of the precipitant solution, the pH of the precipitation reaction system is kept within the aforementioned range, thus achieving the regulation of the solid content of the coprecipitation reaction system.
[0068] In this invention, there are no particular limitations on the solid-liquid separation, as long as the reaction products obtained after the coprecipitation reaction can be separated, for example, by filtration or centrifugation.
[0069] In this invention, preferably, the product obtained from solid-liquid separation is washed, and the washing solvent is preferably water, more preferably hot water, at a temperature of 30-90°C.
[0070] In this invention, the drying method can be a conventional method in the art, such as vacuum drying, freeze drying, air drying, or oven drying. Vacuum heating drying is preferred in this invention. There are no special requirements for the drying temperature and time, as long as the washed product can be dried. For example, the vacuum heating drying temperature is 50-150℃, and the time is 4-24 hours.
[0071] In this invention, step (2) includes: mixing, drying and calcining the precursor, the T-containing compound, the lithium source and the solvent to obtain the nickel-based cathode material.
[0072] In this invention, there are no particular limitations on the mixing conditions, as long as uniform mixing is ensured. Preferably, the mixing conditions include: a stirring speed of 50-1200 rpm and a stirring time of 0.1-6 h.
[0073] In a preferred embodiment of the present invention, T is selected from at least one of Bi, Sc and Y.
[0074] In a preferred embodiment of the present invention, the T-containing compound is selected from at least one of T-containing nitrates, carbonates, bicarbonates, acetates, oxalates, and sulfates, more preferably from at least one of scandium nitrate, scandium acetate, scandium oxalate, yttrium nitrate, yttrium acetate, yttrium oxalate, bismuth nitrate, bismuth acetate, and bismuth oxalate.
[0075] In this invention, the lithium source may exist in the form of a lithium salt, which is preferably selected from at least one of lithium nitrate, lithium chloride, lithium carbonate, lithium hydroxide, lithium oxide, lithium phosphate, lithium dihydrogen phosphate, lithium acetate, and their hydrates.
[0076] In a preferred embodiment of the present invention, the molar ratio of lithium source (calculated as Li), Ni, Co, M and T-containing compound (calculated as T) is (0.9-1.3):(0-1):(0-1):(0-1):(0-0.1), preferably (0.9-1.3):(0.5-0.95):(0-0.5):(0-0.5):(0-0.05), wherein the molar amounts of Ni and T-containing compound are not 0.
[0077] Preferably, the molar ratio of the T-containing compound (calculated as T element) to the precursor (calculated as (Ni+Co+M)) is (0-0.1):1, more preferably (0-0.05):1, for example 0.01:1, 0.02:1, 0.03:1, 0.04:1, 0.05:1, and any value within the range formed by any two of these values.
[0078] Preferably, the molar ratio of the lithium source (calculated as Li) to the precursor (calculated as (Ni+Co+M)) is (0.9-1.3):1, for example, 0.9:1, 0.95:1, 1:1, 1.05:1, 1.1:1, 1.15:1, 1.2:1, 1.3:1, and any value within the range formed by any two of these values.
[0079] In this invention, there is no particular limitation on the type of solvent, as long as it can dissolve the T-containing compound and / or the lithium source. Preferably, the solvent is selected from water.
[0080] In this invention, the amount of solvent can be selected within a wide range. Preferably, the mass ratio of the solvent to the precursor is 2-60, and more preferably 10-60.
[0081] In this invention, the drying method in step (2) is not particularly limited, as long as the solvent in the mixture obtained by mixing the precursor, the T-containing compound, the lithium source, and the solvent can be removed. The drying method includes, but is not limited to, forced-air drying, vacuum drying, freeze-drying, and natural air drying. This invention preferably uses forced-air heating drying. The drying temperature and time are not particularly required, as long as the solvent can be removed. For example, the heating temperature is 40-150℃, preferably 70-120℃. This invention does not limit the drying time; it can be adapted to the drying temperature, as long as the solvent is evaporated.
[0082] In this invention, preferably, the roasting is carried out in an atmosphere furnace, and the roasting atmosphere can be at least one of air, oxygen, and an inert atmosphere such as nitrogen.
[0083] In a preferred embodiment of the present invention, the roasting method is not particularly limited. Preferably, the roasting process includes a first roasting and a second roasting.
[0084] Preferably, the conditions for the first roasting include: a roasting temperature of 300-600℃, such as 300℃, 350℃, 400℃, 450℃, 500℃, 550℃, 600℃, and any value within the range formed by any two of these values; more preferably, the roasting temperature is 450-550℃; preferably, the first roasting time is 1-10h, such as 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, and any value within the range formed by any two of these values; more preferably, the roasting time is 4-8h.
[0085] Preferably, the conditions for the second roasting include: a roasting temperature of 600-1000℃, such as 600℃, 650℃, 700℃, 750℃, 800℃, 850℃, 900℃, 950℃, 1000℃, and any value within the range formed by any two of these values; more preferably, the roasting temperature is 750-900℃; preferably, the first roasting time is 4-48h, such as 4h, 8h, 12h, 16h, 20h, 24h, 28h, 32h, 36h, 40h, 44h, 48h, and any value within the range formed by any two of these values; more preferably, the roasting time is 8-24h.
[0086] According to the method provided by the present invention, there is no particular limitation on the heating rate of the heating process for heating to the first calcination and second calcination temperatures, but it is preferably 0.5-10℃ / min, for example 0.5℃ / min, 1℃ / min, 2℃ / min, 3℃ / min, 5℃ / min, 10℃ / min, and any value within the range formed by any two of these values.
[0087] A third aspect of this invention provides the application of the nickel-based cathode material described in the first aspect or the nickel-based cathode material prepared by the method described in the second aspect in lithium-ion batteries. The inventors of this invention have discovered in their research that using the nickel-based cathode material provided by this invention in lithium-ion batteries can improve the rate discharge performance of lithium-ion batteries.
[0088] The structure of the lithium-ion battery described in this invention is well known to those skilled in the art. Generally, the lithium-ion battery includes a positive electrode, a negative electrode, an electrolyte, and a separator. The positive electrode and the negative electrode can be prepared by coating and drying a composite material containing a positive electrode material and a composite material containing a negative electrode material on their respective current collectors.
[0089] This invention does not particularly limit the composition and preparation method of the positive electrode, negative electrode, electrolyte, and separator; they can be various substances conventionally used in the art. As long as the positive electrode contains the aforementioned nickel-based positive electrode material, it is acceptable. For example, the positive electrode can be prepared using a positive electrode material, a conductive agent, a binder, and a solvent.
[0090] In this invention, the amount of the positive electrode material, conductive agent, and binder is not specifically limited. Preferably, based on the solid content of the positive electrode, the mass content of the positive electrode material is 50-99 wt%, the mass content of the conductive agent is 0.5-25 wt%, and the mass content of the binder is 0.5-25 wt%.
[0091] In this invention, there are no particular restrictions on the conductive agent used in the positive electrode, as long as it is conductive and remains stable within the charge-discharge range. Preferably, the conductive agent is selected from at least one of acetylene black, Ketjen black, artificial graphite, natural graphite, carbon nanotubes, graphene, superconducting carbon, carbon nanofibers, carbon dots, aluminum powder, nickel powder, titanium dioxide, and conductive polymers.
[0092] In this invention, there are no particular limitations on the binder used in the positive electrode, as long as it can provide adhesion between the positive electrode material, the conductive agent, and the current collector. Preferably, the binder is selected from at least one of polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), waterborne acrylic resin, polytetrafluoroethylene (PTFE), polyvinyl butyral (PVB), ethylene-vinyl acetate (EVA), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoroethylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylic resin.
[0093] In this invention, there are no particular limitations on the positive current collector, as long as it has suitable conductivity. Preferably, the material of the positive current collector can be aluminum, nickel, copper, titanium, silver, stainless steel, or carbon material, and the positive current collector can be processed into various forms such as foil, sheet, film, mesh, perforation, or non-woven fabric.
[0094] In a preferred embodiment of the present invention, the solvent used in the positive electrode may be N-methylpyrrolidone.
[0095] The present invention will be described in detail below through embodiments. In the following embodiments and comparative examples,
[0096] Scanning electron microscope (SEM) images were obtained using a ZEISS Merlin scanning electron microscope from ZEISS GmbH, Germany.
[0097] The X-ray diffraction pattern (XRD) was obtained using a Bruker D8 Advance SS X-ray diffractometer from Germany.
[0098] Unless otherwise stated, all raw materials used in the following examples and comparative examples are commercially available products.
[0099] Example 1
[0100] This embodiment illustrates the preparation and evaluation method of the nickel-based cathode material described in this invention.
[0101] (1) Preparation of nickel-based cathode materials
[0102] Prepare a metal salt solution with a total metal concentration of 3 mol / L. The molar ratio of nickel, cobalt, and manganese in the metal salt solution is 8:1:1. Nickel sulfate, cobalt sulfate, and manganese sulfate are used in the preparation process. Prepare a NaOH solution with a concentration of 5 mol / L. Prepare an ammonia solution as a complexing agent with a concentration of 5 mol / L.
[0103] Ammonia solution with a concentration of 0.5 mol / L, accounting for 30% of the reactor volume, was pre-added to the reactor. The aforementioned metal salt solution, NaOH solution, and complexing agent solution were simultaneously added to the reactor to initiate a precipitation reaction. The stirring speed was controlled at 1000 rpm, and the reaction temperature was 55℃. The initial volumetric flow rate ratio of the metal salt solution to the complexing agent solution was controlled at 3. Then, the flow rate of the metal salt solution was kept constant, while the feed flow rate of the complexing agent was controlled, causing the concentration of the complexing agent in the system to gradually increase, and the rate of increase to gradually decrease. The change in the concentration of the complexing agent in the system with reaction time is shown in [Figure showing the change]. Figure 5 The flow rate of the NaOH solution was controlled to maintain the pH of the reaction system at around 11.2 throughout the reaction process. The solid content of the reaction system was 4.5 wt% at 6 hours, and the ammonia concentration at the end of the reaction was approximately 1.06 mol / L. The reaction was stopped after approximately 48 hours when the target particle size was reached. The slurry was then vacuum filtered, washed three times with deionized water, and dried in a vacuum drying oven at 120℃ for 12 hours to obtain the cathode material precursor.
[0104] Take 10g of the above precursor, add lithium source LiOH·H2O and Bi(NO3)3, so that the molar ratio of Li:(Ni+Co+Mn) is 1.02:1 and the molar ratio of Bi:(Ni+Co+Mn) is 0.01:1, then add 200mL of water, stir at 500rpm for 2h to obtain a mixture, heat the mixture to 70℃ until the water is completely evaporated. Then, put it into a crucible for stepwise sintering. First step: heat from room temperature to 450℃ at 5℃ / min and hold for 6h. Second step: heat from 450℃ to 800℃ at 5℃ / min and hold for 12h. Then cool naturally to obtain nickel-based cathode material.
[0105] (2) Evaluation of nickel-based cathode materials
[0106] The nickel-based cathode material prepared above was characterized by SEM, such as... Figure 1 As shown in the figure, the preparation method provided by this invention can yield a nickel-based cathode material with good sphericity. This cathode material is formed by the stacking of primary particles into secondary microspheres. The size of the primary particles is between 0.1 and 2 μm, and the size of the secondary microspheres is approximately 9.5 μm.
[0107] The nickel-based cathode material prepared above was characterized by XRD, and the results are as follows: Figure 2 As shown in the figure, the main diffraction peaks of the nickel-based cathode material prepared by the method provided in this invention are consistent with those of the hexagonal α-NaFeO2, indicating the formation of a good layered crystal structure. The intensity ratio of the (003) diffraction peak in the 2θ range of 18°-20° to the (104) diffraction peak in the 43.5°-45° range is 1.99, indicating a very low lithium-nickel mixing ratio in the nickel-based cathode material. In the 2θ range of 63°-66°, the intensity ratio of the (110) diffraction peak to the (108) diffraction peak is 1.15, indicating that the (110) crystal plane is sufficiently exposed, which is beneficial for the migration of lithium ions in the nickel-based cathode material.
[0108] In addition, the XRD pattern shows that there are no impurity peaks in the cathode material, indicating that the added Bi component has completely entered the crystal lattice of the material.
[0109] The above-mentioned positive electrode material, acetylene black, and 10% (w / w) polyvinylidene fluoride solution were mixed evenly according to a mass ratio of positive electrode material: acetylene black: polyvinylidene fluoride 90:5:5. The mixture was then coated onto aluminum foil, the solvent was dried, and the foil was sliced to obtain the positive electrode sheet. The negative electrode sheet used lithium metal. The separator used was a Celllgard 2400 polypropylene separator. The electrolyte used was a liquid electrolyte, with a solvent of ethylene carbonate (EC) and dimethyl carbonate (DMC) in a volume ratio of 1:1. The solute was lithium hexafluorophosphate (LiPF6) with a molar concentration of 1 mol / L. The cells were assembled into 2025-type coin cells in an inert atmosphere glove box, where the moisture and oxygen content were below 0.1 ppm.
[0110] The electrochemical performance of the nickel-based cathode material was measured in the charge / discharge voltage range of 2.8-4.3V. The discharge capacity at 0.1C rate was 10.0mAh, and the discharge capacity at 1C rate was 9.52mAh. The discharge capacity at 1C rate can reach 95.2% of the discharge capacity at 0.1C rate.
[0111] Example 2
[0112] This embodiment illustrates the preparation and evaluation method of the nickel-based cathode material described in this invention.
[0113] (1) Preparation of nickel-based cathode materials
[0114] Prepare a metal salt solution with a total metal concentration of 2 mol / L. The molar ratio of nickel, cobalt, and aluminum in the metal salt solution is 8:1.5:0.5. Nickel sulfate, cobalt sulfate, and aluminum sulfate are used in the preparation process. Prepare a NaOH solution with a concentration of 5 mol / L. Prepare an ammonia solution as a complexing agent with a concentration of 4 mol / L.
[0115] Ammonia solution with a concentration of 0.5 mol / L, accounting for 20% of the reactor volume, was pre-added to the reactor. The aforementioned metal salt solution, NaOH solution, and complexing agent solution were simultaneously added to the reactor to initiate a precipitation reaction. The stirring speed was controlled at 800 rpm, and the reaction temperature at 50°C. The initial volumetric flow rate ratio of the metal salt solution to the complexing agent solution was controlled at 3. Then, the flow rate of the metal salt solution was kept constant, while the feed flow rate of the complexing agent was controlled, causing the concentration of the complexing agent in the system to gradually increase, and the rate of increase to gradually decrease. The change in the concentration of the complexing agent in the system with reaction time was the same as in Example 1. The flow rate of the NaOH solution was controlled to maintain the pH value of the reaction system at around 11.4 throughout the reaction process. The solid content of the reaction system at 6 hours was 4.1 wt%, and the concentration of ammonia solution in the system at the end of the reaction was approximately 1.06 mol / L. The reaction was stopped after the target particle size was reached after about 48 hours. The slurry was then vacuum filtered, washed three times with deionized water, and dried in a vacuum drying oven at 120°C for 12 hours to obtain the cathode material precursor.
[0116] Take 10g of the above precursor, add lithium source LiNO3 and Sc(Ac)3, making the molar ratio of Li:(Ni+Co+Al) 1.02:1 and the molar ratio of Sc:(Ni+Co+Al) 0.01, then add 300mL of water, stir at 800rpm for 1h to obtain a mixture, heat the mixture to 80℃ until the water completely evaporates. Then, put it into a crucible for stepwise sintering. First step: heat from room temperature to 480℃ at 5℃ / min and hold for 6h. Second step: heat from 480℃ to 820℃ at 5℃ / min and hold for 12h. After natural cooling, obtain nickel-based cathode material.
[0117] (2) Evaluation of nickel-based cathode materials
[0118] The prepared nickel-based cathode material was subjected to SEM and XRD tests. The SEM image is shown below. Figure 3 As shown, with Figure 1 Similar. From Figure 3 The image shows a nickel-based cathode material with good sphericity, which is formed by the stacking of primary particles into secondary microspheres. The size of the primary particles is between 0.02 and 0.7 μm, and the size of the secondary microspheres is approximately 10 μm.
[0119] XRD pattern of nickel-based cathode material as shown in Figure Figure 4 As shown, with Figure 2 Similar. From Figure 4As can be seen, the main diffraction peaks of the nickel-based cathode material are consistent with those of the hexagonal α-NaFeO2 structure, indicating the formation of a good layered crystal structure. The intensity ratio of the (003) diffraction peak in the 2θ range of 18°-20° to the (104) diffraction peak in the 43.5°-45° range is 1.99, indicating a very low lithium-nickel mixing ratio in the nickel-based cathode material. In the 2θ range of 63°-66°, the intensity ratio of the (110) diffraction peak in the (108) diffraction peak is 1.12, indicating that the (110) crystal plane is sufficiently exposed, which is beneficial for the migration of lithium ions in the nickel-based cathode material.
[0120] In addition, the XRD pattern shows that there are no impurity peaks in the cathode material, indicating that the added Sc component has completely entered the crystal lattice of the material.
[0121] Lithium-ion batteries were prepared according to the method described in Example 1.
[0122] The electrochemical performance of the nickel-based cathode material was measured in the charge / discharge voltage range of 2.8-4.3V. The discharge capacity at 0.1C rate was 10.0mAh, and the discharge capacity at 1C rate was 9.32mAh. The discharge capacity at 1C rate can reach 93.2% of the discharge capacity at 0.1C rate.
[0123] Example 3
[0124] This embodiment illustrates the preparation and evaluation method of the nickel-based cathode material described in this invention.
[0125] (1) Preparation of nickel-based cathode materials
[0126] The cathode material precursor was prepared according to the method in Example 1.
[0127] Take 10g of the above precursor, add lithium source LiOH·H2O and Bi2(C2O4)3 to make the molar ratio of Li:(Ni+Co+Mn) 1.05:1 and the molar ratio of Bi:(Ni+Co+Mn) 0.03, then add 400mL of water and stir at 300rpm for 4h to obtain a mixture. Heat the mixture to 120℃ until the water completely evaporates. Then, put it into a crucible for stepwise sintering. First step: heat from room temperature to 500℃ at 5℃ / min and hold for 7h. Second step: heat from 500℃ to 820℃ at 5℃ / min and hold for 12h. Then, cool naturally to obtain nickel-based cathode material.
[0128] (2) Evaluation of nickel-based cathode materials
[0129] The prepared nickel-based cathode material was subjected to SEM and XRD tests. The SEM images are shown in the figure. Figure 1 Similarly, the XRD patterns of the nickel-based cathode materials show that the intensity ratio of the diffraction peaks of the (003) and (104) crystal planes is 1.95; and the intensity ratio of the diffraction peaks of the (110) and (108) crystal planes is 1.14.
[0130] In addition, the XRD pattern shows that there are no impurity peaks in the cathode material, indicating that the added Bi component has completely entered the crystal lattice of the material.
[0131] Lithium-ion batteries were prepared according to the method described in Example 1.
[0132] The electrochemical performance of the cathode material was measured within a charge / discharge voltage range of 2.8–4.3 V. The discharge capacity at 0.1 C rate was 10.0 mAh, and the discharge capacity at 1 C rate was 9.51 mAh. The discharge capacity at 1 C rate can reach 95.1% of the discharge capacity at 0.1 C rate.
[0133] Example 4
[0134] This embodiment illustrates the preparation and evaluation method of the nickel-based cathode material described in this invention.
[0135] (1) Preparation of nickel-based cathode materials
[0136] The cathode material precursor was prepared according to the method in Example 1.
[0137] Take 10g of the above precursor, add lithium source LiAc and Y(NO3)3 to make the molar ratio of Li:(Ni+Co+Mn) 1.05:1 and the molar ratio of Y:(Ni+Co+Mn) 0.03, then add 300mL of water and stir at 1000rpm for 0.5h to obtain a mixture. Heat the mixture to 100℃ until the water is completely evaporated. Then, put it into a crucible for stepwise sintering. First step: heat from room temperature to 550℃ at 5℃ / min and hold for 6h. Second step: heat from 550℃ to 750℃ at 5℃ / min and hold for 18h. Then, cool naturally to obtain nickel-based cathode material.
[0138] (2) Evaluation of nickel-based cathode materials
[0139] The prepared nickel-based cathode material was subjected to SEM and XRD tests. The SEM images are shown in the figure. Figure 1 Similarly, the XRD patterns of the nickel-based cathode materials show that the intensity ratio of the diffraction peaks of the (003) and (104) crystal planes is 1.83; and the intensity ratio of the diffraction peaks of the (110) and (108) crystal planes is 1.05.
[0140] In addition, the XRD pattern shows that there are no impurity peaks in the cathode material, indicating that the added Y component has completely entered the crystal lattice of the material.
[0141] Lithium-ion batteries were prepared according to the method described in Example 1.
[0142] The electrochemical performance of the cathode material was measured in the charge / discharge voltage range of 2.8-4.3V. The discharge capacity at 0.1C rate was 10.0mAh, and the discharge capacity at 1C rate was 9.28mAh. The discharge capacity at 1C rate can reach 92.8% of the discharge capacity at 0.1C rate.
[0143] In summary, the nickel-based cathode material prepared by the method provided in this invention has high rate performance.
[0144] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A nickel-based cathode material, characterized in that, The chemical composition of the nickel-based cathode material is Li a Ni x Co y M z T p O2; wherein, 0.9≤a≤1.3, 0<x≤1, 0≤y<1, 0≤z<1, 0<p≤0.1, and x+y+z=1; M is selected from at least one element of group VIIB and group IIIA, T is selected from at least one element of group IIIB and group VA, and T is doped in the lattice of the nickel-based cathode material; In the X-ray diffraction pattern of the nickel-based cathode material, the ratio of the intensities of the (003) and (104) crystal plane diffraction peaks, measured by peak height, is not less than 1.5; In the X-ray diffraction pattern of the nickel-based cathode material, the ratio of the intensities of the (110) and (108) crystal plane diffraction peaks, measured by peak height, is not less than 1.
2. The nickel-based cathode material according to claim 1, wherein, The T is selected from at least one of Bi, Sc and Y.
3. The nickel-based cathode material according to claim 1 or 2, wherein, M is selected from Mn and / or Al.
4. The nickel-based cathode material according to claim 1 or 2, wherein, 0.9≤a≤1.3, 0.5≤x≤0.95, 0≤y≤0.5, 0≤z≤0.5, 0<p≤0.05, and x+y+z=1.
5. The nickel-based cathode material according to claim 1 or 2, wherein, In the X-ray diffraction pattern of the nickel-based cathode material, the ratio of the intensities of the (003) and (104) crystal plane diffraction peaks, measured by peak height, is not less than 1.
7.
6. The nickel-based cathode material according to claim 1 or 2, wherein, In the X-ray diffraction pattern of the nickel-based cathode material, the ratio of the intensities of the (110) and (108) crystal plane diffraction peaks, measured by peak height, is not less than 1.
05.
7. The nickel-based cathode material according to claim 1 or 2, wherein, The nickel-based cathode material is formed by the agglomeration of primary particles into secondary microspheres, and the particle size of the secondary microspheres is 1-30 μm.
8. The nickel-based cathode material according to claim 7, wherein, The secondary microspheres have a particle size of 1-20 μm.
9. A method for preparing the nickel-based cathode material according to any one of claims 1-8, characterized in that, The method includes the following steps: (1) The metal salt solution, precipitant solution and complexing agent solution are subjected to a co-precipitation reaction to obtain the precursor; (2) The precursor, the T-containing compound, the lithium source and the solvent are mixed, dried and calcined to obtain the nickel-based cathode material; The metal salt solution contains at least one of the elements Ni, Co, and M.
10. The method according to claim 9, wherein, The mass ratio of the solvent to the precursor in step (2) is 2-60.
11. The method according to claim 9 or 10, wherein, The mixing conditions in step (2) include: a stirring speed of 50-1200 rpm and a stirring time of 0.1-6 h.
12. The method according to claim 9 or 10, wherein, The drying conditions described in step (2) include a temperature of 40-150℃.
13. The method according to claim 12, wherein, The drying conditions described in step (2) include a temperature of 70-120℃.
14. The method according to claim 9 or 10, wherein, In step (2), the roasting includes a first roasting and a second roasting.
15. The method according to claim 14, wherein, The conditions for the first roasting include: a temperature of 300-600℃ and a time of 1-10h.
16. The method according to claim 15, wherein, The conditions for the first roasting include: a temperature of 450-550℃ and a time of 4-8 hours.
17. The method according to claim 14, wherein, The conditions for the second calcination include: a temperature of 600-1000℃ and a time of 4-48h.
18. The method according to claim 17, wherein, The conditions for the second roasting include: a temperature of 750-900℃ and a time of 8-24h.
19. The method according to claim 9 or 10, wherein, The T-containing compound is selected from at least one of the following: nitrates, carbonates, bicarbonates, acetates, oxalates, and sulfates containing T.
20. The method according to claim 9 or 10, wherein, The lithium source is selected from at least one of lithium nitrate, lithium chloride, lithium carbonate, lithium hydroxide, lithium oxide, lithium phosphate, lithium dihydrogen phosphate, lithium acetate, and their hydrates.
21. The method according to claim 9 or 10, wherein, The solvent is selected from solvents capable of dissolving the T-containing compound and / or lithium source.
22. The method according to claim 20, wherein, The solvent is water.
23. The method according to claim 9 or 10, wherein, In step (1), the concentration of the complexing agent in the coprecipitation reaction system gradually increases, and the rate of change of the concentration of the complexing agent gradually decreases.
24. The method according to claim 23, wherein, The concentration change rate of the complexing agent is less than 1 mol / L·h.
25. The method according to claim 24, wherein, The concentration of the complexing agent changes at a rate of 0.001-1 mol / L·h.
26. The method according to claim 25, wherein, The concentration change rate of the complexing agent is selected to be 0.001-0.5 mol / L·h.
27. The method according to claim 9 or 10, wherein, The coprecipitation reaction time is denoted as R hours. In the first 1 / 8 of R hours after the start of the reaction, the concentration change rate of the complexing agent is not less than 0.021 mol / L·h.
28. The method according to claim 9 or 10, wherein, In the coprecipitation reaction system, the time from the addition of the complexing agent to reaching a concentration of no less than 80% of the complexing agent concentration at the end of the reaction shall not exceed 1 / 4R hour.
29. The method according to claim 9 or 10, wherein, At the end of the reaction, the concentration of the complexing agent is 0.05-2 mol / L.
30. The method according to claim 29, wherein, At the end of the reaction, the concentration of the complexing agent is 0.05-1.2 mol / L.
31. The method according to claim 9 or 10, wherein, The coprecipitation reaction time is denoted as R hours. In the first 1 / 8 of R hours after the start of the reaction, the solid content of the precipitation reaction system is not higher than 7 wt%.
32. The method according to claim 30, wherein, The coprecipitation reaction time is denoted as R hours. In the first 1 / 8 of R hours after the start of the reaction, the solid content of the precipitation reaction system is not higher than 5 wt%.
33. The method according to claim 9 or 10, wherein, The conditions for the coprecipitation reaction include: a temperature of 20-70℃, a pH value of 8-14, and a reaction time of not less than 10 hours.
34. The method according to claim 33, wherein, The conditions for the coprecipitation reaction include: a temperature of 45-60℃, a pH of 10-12, and a reaction time of 12-96h.
35. The method according to claim 9 or 10, wherein, The coprecipitation reaction was carried out under stirring conditions, with a stirring speed of 50-1200 r / min.
36. The method according to claim 35, wherein, The coprecipitation reaction was carried out under stirring conditions at a speed of 600-1200 r / min.
37. The method according to claim 9 or 10, wherein, The concentration of the metal salt solution is 0.01-5 mol / L, calculated by metal element.
38. The method according to claim 37, wherein, The concentration of the metal salt solution is 0.01-4 mol / L, calculated by metal element.
39. The method according to claim 9 or 10, wherein, The concentration of the precipitant solution is 0.01-16 mol / L.
40. The method according to claim 39, wherein, The concentration of the precipitant solution is 2-12 mol / L.
41. The method according to claim 9 or 10, wherein, The concentration of the complexing agent solution is 0.01-16 mol / L.
42. The method according to claim 41, wherein, The concentration of the complexing agent solution is 2-15 mol / L.
43. The method according to claim 9 or 10, wherein, The complexing agent is selected from at least one of ammonium ion donors, alkanolamine complexing agents, aminocarboxylic acid complexing agents, hydroxyaminocarboxylic acid complexing agents, carboxylate complexing agents, and thiocyanate complexing agents.
44. The method according to claim 9 or 10, wherein, The precipitant is selected from at least one of alkali metal hydroxides, carbonates, and bicarbonates, wherein the alkali metal is selected from at least one of Na, K, and Li.
45. The application of the nickel-based cathode material according to any one of claims 1-8 in lithium-ion batteries.
Citation Information
Patent Citations
High-nickel ternary positive electrode material of lithium ion battery and preparation method of high-nickel ternary positive electrode material
CN105633395A
Cathode material and preparation method and application thereof
CN111435738A
